How to make an apple pie from scratch : in search of the recipe for our universe-from the origins of atoms to the big bang - Cliff, Harry (Harry Victor) (Picador, 2021)
"By an experimental physicist who works on the Large Hadron Collider, a mind-altering look at the foundational questions bedeviling modern physics, among them: Where does matter come from? Carl Sagan famously said, "If you wish to make an apple pie from scratch, you must first invent the universe." But what fundamental matter is the universe made of? What banged in the Big Bang? And how did that matter arise from nothing into the world we now know? In How to Make an Apple Pie from Scratch, Harry Cliff--a University of Cambridge particle physicist, researcher on the Large Hadron Collider, and acclaimed science presenter--sets out in pursuit of answers. He ventures to the largest underground research facility in the world, deep beneath Italy's Gran Sasso mountains, where scientists look into the heart of the Sun using the most elusive of particles, the ghostly neutrino. He visits CERN in Switzerland to behold the 'Antimatter Factory,' where this stuff of science fiction is manufactured daily (and we're close to knowing whether it falls up). Cliff illuminates the history of physics and chemistry that brought us to our present understanding--and misunderstandings--of the world, while offering readers a front row seat to the dramatically unfolding quest to unlock, at long last, the secrets of our universe. A transfixing deep-dive into the origins of the world, How to Make an Apple Pie from Scratch investigates not just the makeup of our universe, but the awe-inspiring, improbable fact that it exists at all"--